2013
DOI: 10.1038/jcbfm.2013.120
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Treatment for Experimental Stroke: An Individual Animal Meta-Analysis

Abstract: Preclinical studies suggest progesterone is neuroprotective after cerebral ischemia. The gold standard for assessing intervention effects across studies within and between subgroups is to use meta-analysis based on individual animal data (IAD). Preclinical studies of progesterone in experimental stroke were identified from searches of electronic databases and reference lists. Corresponding authors of papers of interest were contacted to obtain IAD and, if unavailable, summary data were obtained from the public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 51 publications
2
33
0
1
Order By: Relevance
“…Progesterone was administered at 1, 6, and 24 h after MCAO. This dose and treatment regimen have been shown to be neuroprotective in previous studies using intraperitoneal or subcutaneous injections of progesterone (Wong et al, 2013). …”
Section: Methodsmentioning
confidence: 86%
See 4 more Smart Citations
“…Progesterone was administered at 1, 6, and 24 h after MCAO. This dose and treatment regimen have been shown to be neuroprotective in previous studies using intraperitoneal or subcutaneous injections of progesterone (Wong et al, 2013). …”
Section: Methodsmentioning
confidence: 86%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 progesterone treatment in male mice (Gibson and Murphy, 2004) while another study showed no effect of progesterone on mortality rate in ovariectomised females and in aged females (Gibson et al, 2011). A recent meta-analysis based on individual animal data concluded that progesterone was associated with an increase in death (Wong et al, 2013). Our results show that progesterone oleogel administered by intranasal route decreased the mortality rate.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations